Helicobacter Pylorosis in Children: Features of Diagnosis and Treatment - Худайберганова Н. Х.; Аликулов И. Т. (European Science Publishing, 2023)
The article presents literature data on the mechanisms and role of Helicobacter pylori infection in the development of diseases of the gastroduodenal zone, features of diagnosis and therapy.
Keywords: Helicobacter pylori, pathogenicity factors, eradication therapy.